FSO System Performance Enhancement: Receiver Impact - Ghoname, Sherif; El Aziz, Ahmed Abd; Fayed, Heba A.; H. Aly, Moustafa (Journal of Advanced Research in Applied Mechanics, 2020)
The atmospheric conditions such as fog and humidity are the main causes of attenuation of the free space optical (FSO) communication link. This leads to a reduction in the received power which can cause a drop in the performance of FSO link. This paper investigates the performance of an FSO system at different wavelengths 850, 950and 1550 nm at a distance up to 1 km under the effect of fog and humidity. Different transmitter divergence angles and receiver aperture diameters are studied using PIN photodiode and avalanche photodiode (APD). The obtained results show a remarkable improvement achieving maximum power received, data rate and signal to noise ratio (SNR) and minimum bit error rate (BER) for nonreturn-to-zero on-off keying(NRZ-OOK) modulation technique.